TATA NIAGA KAYU KARET SERTA PENGARUH HARGA KARET TERHADAP PENDAPATAN PEMASOK KAYU KARET: STUDI KASUS DESA SEMBAWA, SUMATERA SELATAN - Iman Satra Nugraha; Aprizal Alamsyah; Dwi Shinta Agustina (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2018)
This study aims to determine replanting potential and marketing channels of rubber wood and the influence of rubber prices on the revenues of rubber wood supplier. As a case study, the study was conducted in Sembawa Village, Banyuasin District, South Sumatra. Data was collected through interview technique with respondent by using structured questionnaire. The respondents consisted of rubber smallholders and large estate that undertake rubber replanting, as well as rubber wood suppliers who take rubber wood from rubber replanting. Respondents were selected purposively. Data were analyzed qualitatively and quantitatively. The results indicated that the minimum rubber replanting area per annum was 917 hectare with the rubber wood potential resulted from such replanting was 73,360 m per year. The observed marketing channels of rubber wood was planters-suppliers-wood processing factories / brick industries. The incomes of rubber wood supplier were influenced by rubber resin prices changes. The rubber prices declined by 40%, the supplier’s incomes of rubber wood from large estates was also decreased by 59%, and the suppliers' incomes of rubber wood from smallholder decreased by 54%.